Toxic Epidermal Necrolysis (TEN)/Stevens-Johnson Syndrome (SJS) Epidemiology and Mortality Rate at King Fahad Specialist Hospital (KFSH) in Qassim Region of Saudi Arabia: A Retrospective Study - Abdullah Alajaji; Jagannath Chandra Shekaran; Omar Mohammed Aldhabbah; Hajar Abdullah Alhindi; Nouf Salem Almazyad; Ziyad Abdulrahman Aljutayli; Saleh Abaalkhail; Saleh Alfouzan (Dermatology Research and Practice)
Background. Toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) are life-threatening conditions caused by drug reactions. There are multiple causative drugs and different risk factors associated with SJS/TEN. Objectives. To study the epidemiology of SJS/TEN and associated mortality rate in Qassim region, Saudi Arabia. Methodology. A retrospective chart review of all patients with the diagnosis of SJS/TEN who were admitted to King Fahad Specialist Hospital (KFSH) in Qassim region, Saudi Arabia, for the period between Jan 2014 to Jan 2019. The Careware information health system is used at KFSH, and patients were identified searching the diagnosis SJS/TEN. Results. Total of 10 patients with diagnosis of SJS/TEN were admitted to KFSH for the period from Jan 2014 to Jan 2019. Antibiotics were the culprit in 5 out of 10 patients. 9 out of 10 patients survived with good outcome. One patient with the diagnosis of TEN died, given extensive skin involvement complicated by sepsis. Conclusion. Despite the limitation of this study given small sample size, this is the first study of its kind that discusses the epidemiology of SJS/TEN in Saudi Arabia. We found the estimated incidence rate of SJS/TEN in Qassim region to be 7.6 cases per million person-years. Antibiotics and antiepileptics were the culprits in 8 out of 10 patients.